Zeros of a family of hypergeometric para-orthogonal polynomials on the unit circle - Dimitrov, Dimitar K.; Ranga, A. Sri (Wiley, 2013)
Para-orthogonal polynomials derived from orthogonal polynomials on the unit circle are known to have all their zeros on the unit circle. In this note we study the zeros of a family of hypergeometric para-orthogonal polynomials. As tools to study these polynomials, we obtain new results which can be considered as extensions of certain classical results associated with three term recurrence relations and differential equations satisfied by orthogonal polynomials on the real line. One of these results which might be considered as an extension of the classical Sturm comparison theorem, enables us to obtain monotonicity with respect to the parameters for the zeros of these para-orthogonal polynomials. Finally, a monotonicity of the zeros of Meixner-Pollaczek polynomials is proved. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: 30C15; 33C45; 42C05; Hypergeometric polynomials; Para-orthogonal polynomials; Szego polynomials